Racial and ethnic differences in the health of older Americans - Martin, Linda G., 1947-; Soldo, Beth J. (National Academy Press, 1997)
Older Americans, even the oldest, can now expect to live years longer than those who reached the same ages even a few decades ago. Although survival has improved for all racial and ethnic groups, strong differences persist, both in life expectancy and in the causes of disability and death at older ages. This volume examines trends in mortality rates and selected causes of disability (cardiovascular disease, dementia) for older people of different racial and ethnic groups.